Correlation of Serum Vitamin D and Calcium Levels between Outdoor and Indoor Working Professionals in Dhaka City, Bangladesh - Tasrin, Tarana; Ferdousi, Shahnila; Sultan, Md Kamal; Mozaffor, Miliva (Community Based Medical Journal, 2023)
A cross-sectional study was conducted in the Department of Biochemistry, Dhaka Medical College, Dhaka, Bangladesh, from July 2018 to June 2019, to compare serum vitamin D levels and observe its correlation with serum calcium levels among the outdoor and indoor working professionals. A total of 101 indoor and outdoor workers of different sectors living in Dhaka city participated in this study. All study subjects were divided into two groups: outdoor workers were in group A (n=35) and indoor workers were in group B (n=66). Estimation of serum vitamin D3 was done by chemiluminescent microparticle immunoassay, while serum calcium was measured using Arsenazo-III dye method. The mean age of the study participants was 38.72±6.88 years, ranging between 25 and 52 years. Among the study participants, 64(63.4%) were male and 37(36.6%) were female. Among outdoor workers, most were from Traffic Police Services (83%) and the rest were street hawkers (17%). Indoor workers were recruited from the hospital – nurses (32%), doctors (27%), administrative employees (21%), hospital ward assistants (12%) and medical technicians (8%). Serum vitamin D3 level was found higher in outdoor workers than that of indoor workers (19.35±5.67 ng/ml vs. 14.17±4.18 ng/ml) and the difference was statistically significant (P<0.001). Serum calcium level was lower in outdoor workers than that of indoor workers (8.82±0.54 mg/dl vs. 9.08±1.08 mg/dl); however, the difference was not statistically significant (P>0.05). Moreover, no significant correlation was observed between serum vitamin D and calcium levels in both outdoor (r= – 0.117; P=0.510) and indoor (r= – 0.163; P=0.196) groups. CBMJ 2023 January: Vol. 12 No. 01 P: 87-92